Development of Islamic Cultural History Learning Materials in Indonesia’s 2013 Curriculum - Rofik, Rofik (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Curriculum development from Competency-Based Curriculum (KBK 2004) to Education Unit Level Curriculum (KTSP 2006) and Curriculum 2013 occurred in a relatively short period. In short, the timespan of this kind of development then gives rise to various responses from Education practitioners. This study aims to explain how teachers can take steps to develop the materials of the Islamic Cultural History subject in the Islamic Senior High School’s 2013 Curriculum. This type of study is a literature study. The development of learning materials starts with making a mapping or mutual relationship between one Basic Competency with other Basic competencies. The results of the mapping have implications for the emergence of the formulation of the Main Materials. The next step is to develop indicators of Competency Achievement based on Knowledge Basic Competencies and Skills. Based on Competency Achievement Indicators, they are formulated into learning materials, which are the scope of the primary materials. Thus, there will be harmony between learning materials with competence. Further, this harmony leads to the formulation of attitudes or values achieved after learning the Learning materials. The results of this study will facilitate teachers in the preparation of the Syllabus to the Learning Implementation Plan (RPP).